Cálculo de Fotoperíodo y Elaboración del Diagrama solar del Cantón Latacunga en el período 2016-2017. - Villarroel Basantes, Erik Ariel (2017)
The present research project aims to calculate the photoperiod, linked to the set of processes that occur in plants with exposure to sunlight which are responsible for regulating the main physiological functions in plant species in their development of Photosynthesis that binds with plant growth. Which is used as a parameter in the alteration of the solar cycle, which allows us to calculate the amount of sunlight that the crops are exposed in Canton Latacunga. By means of the solar diagram allows us to see the percentages of the intensity of sunlight per hour that enters the Canton, also must take into account the position of the sun since there are obstacles that do not allow the entrance, which in the calculation there will be a variation in the percentage of sunlight.However, when doing this project we can verify the percentage of the photoperiod that the crops of the Canton Latacunga are exposed to the sun, average the position of the sun. First of all, because depending on the location the photoperiod varies, in the Canton Latacunga has a duration 12 hours in the day, taken in that at 6:00 a.m. to 10:00 a.m., the Canton do not have a very high intensity with a percentage of 46.69% of photoperiod that the crops are exposed in essence in the first 4 hours of the day; unlike the following 3 hours from 11:00 a.m. to 1:00 p.m., we have a greater amount of intensity with 91.01% of the photoperiod than the crops, being very beneficial for the crops to have a better environment for the realization of the photosynthesis and from 14:00 to 18:00 has a 51.35% photoperiod percentage that crops are exposed at the end of the day. This allows us to verify that the amount of sunlight is adequate for Corn, Bean, and Potato crops, but its phenological cycle is long.